GENRE-STYLE CONSTANTS OF CHAMBER SYMPHONY BY E. STANKOVYCH - Mozgalova, Nataliia; Novosadova, Anna; Novosadov, Yaroslav; Pakholchak, Yevheniia; Shcholokova, Olga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The originality of the creative handwriting of Ukrainian composers of the end of the ХХ and the first quarter of the ХХІ century is becoming an urgent research problem of our time. A large number of components of the musical language of artistic compositions, understanding of new value orientations, genre-style synthesis - these and other features constitute the poetics of the work of domestic artists of the mentioned period. E. Stankovych took an active place among the constellation of Ukrainian composers of the end of the 20th and the first quarter of the 21st century. The article emphasizes that the chamber symphony genre in the composer's work shows the peculiarities of his creative handwriting. It was determined that the composer's legacy of E. Stankovych, in particular the study of his chamber symphonies, is a production for the training of teachers of artistic disciplines. After all, chamber symphonies reflect constant reforms in the field of musical language and composer's thinking. The purpose of the research is to identify genre and stylistic features of chamber symphonies by E. Stankovych. To achieve the goal, historiographical, genre-stylistic and comparative research methods were used. The genre-style model of E. Stankovich's chamber symphonies shows the specificity of postmodern art, which takes place in genre synthesis, understanding the semantic potential of timbre, and transformation of images. Fifteen chamber symphonies of E. Stankovych have a common principle of construction, which gives grounds for confirming the opinion about the emergence of the author's metastyle.